PERHITUNGAN HARGA POKOK PRODUKSI PADA CV. DESIGN KREASINDO SAMARINDA - Sudrajat, Kuat (EKONOMIA, 2013)
Problems of this research what is CV. Design Kreasindo have precisely in calculating cost of goods manufactured use traditional method, because only pursuant to one cost driver of expense of that is production volume.Theory base whichÂ  used in this research is Cost Accounting. Hypothesis in this research is usage of system of Activity Based Costing by CV. Design Kreasindo very precise because will yield more accurate information regarding calculation of cost of goods manufactured where its result can be compared to lower of traditional systemAnalyzer the utilized is system of Activity Based Costing in calculation of cost of goods manufactured, this system utilize more than one pemicu of expense of for the cost allocation of overhead to each product.Result of fundamental price survey ofÂ  production CV. Design Kreasindo to three product of furniture taken as sampel use system of Activity Based Costing menunjukan of[is existence of price difference compared to system calculation of company, that is for the product of Workbench equal to Rp 36.529,00 or 2,10% smaller each;every its unit, smaller File difference cupboard;locker equal to Rp 304.039,00 or 11,11% per unit , and bigger Rack difference shoe of Rp 301.664,00 or 18,05% per unit. Result of research use approach of this method also, yielding data in the form of cost-saving of factory overhead that is BOP Workbench product 4,89 is% lower, Cupboard;Locker file product 7,91 is% lower.Conclusion that calculation of cost of goods manufactured use system of Activity Based Costing more precise, because encumbering of expense of overhead at each product charged against by some driver cost, so that at ABC system activity cost allocation system have been able to to each;every product of furniture precisely pursuant to consumption ofis each activity.